Altered expression of cell cycle regulators p21, p27, and p53 in tumors of salivary glands and paranasal sinuses - Affolter, Annette; Helmbrecht, Stefanie; Finger, Sonja; Hörmann, Karl; Götte, Karl (Oncology reports, 2005)
CIP/KIP family proteins entitled p21WAF1/CIP1 and p27KIP1 have key positions in cell cycle regulation leading to an arrest of cell proliferation. They are supposed to enable a repair process of DNA damage. In several human tumors, a loss of these proteins is associated with poor clinical outcome. The role of these cell cycle regulators in tumors of salivary gland and paranasal sinus origin is still unclear. In this study it was intended to demonstrate and compare the expression of p21, p27, and p53 in benign and malignant tumors of salivary glands and paranasal sinuses. Protein expression was detected by conventional immunohistochemistry (IHC). Additionally, we performed tyramide signal amplified immunohistochemistry (TSA-IHC) for p21 and p53 levels. Nine adenoid cystic carcinomas, 5 adenocarcinomas, 4 cylindrical cell carcinomas, as well as 30 pleomorphic adenomas and 26 inverted papillomas, were studied. In 78% of all adenoid cystic carcinomas a complete loss of p27 expression could be identified, whereas 60% of the adenocarcinomas overexpressed the protein. The majority of cylindrical cell carcinomas showed distinct cytoplasmic accumulation of p27. All malignant tumors turned out to be positive for p21 after performing TSA-IHC, although 72% of those samples had shown weak to negative protein levels in conventional immunostaining. Immunohistochemical results of CIP/KIP proteins were compared to p53 expression as well as to main clinical parameters. The study sheds new light upon the role of CIP/KIP protein family in tumors of salivary glands and paranasal sinuses. Furthermore, it is the first description of p21 and p53 TSA-IHC in these tumor types.